The alteration of oral microbiota before and after training in swimmers: Oral microbiota of swimmers - Eken, Başak Funda; Akkoç, Orkun; Yücesir, İlker; Akmansoy, Şükrü Can; Kadir , Tanju; Ulucan, Korkut (Cellular and Molecular Biology, 2023)
We aimed to analyze the effect of acute exercise on oral microbiota in regularly trained swimmers. As environmental factors may affect the oral microbiota; we also aimed to analyze the short-duration effect of swimming training on the oral bacteria relative difference in swimmers. Saliva samples of 20 swimmers both before and after the training were used for the oral microbiota metagenesis. The next-generation sequencing method targeting 16S rDNA gene fragments was used for genotyping. The Wilcoxon signed-rank test was used for the statistical evaluation of the taxons. The alfa diversity comparisons were assessed with the One-Way ANOVA, and the Kruskal-Wallis test was used to determine bacterial diversity. Decayed- Missed- Filled total (DMF-T) scores were the indicators of oral hygiene. A comparison of the before and after exercise microbiota of the swimmers gave rise to a statistically significant difference for Firmicutes (p=0.014) and Bacteroidetes (p=0.007) phylum; Clostridia (p=0.006) and Bacilli (p=0.048) classes; Clostridiales (p=0.004), Entomoplasmatales (p=0.009) and Bacillales (p=0.006) for ordo; Lachnospiraceae (p=0.001) family and Stenotrophomonas (p=0.013) genus. Although there were some differences within the other taxa of the bacteria, all were statistically insignificant. Streptococcus, Pseudomonas and Rothia mucilaginosa showed a correlation with the DMF-T values in swimmers. This study was the first in Turkish swimmers to investigate the relative abundance of oral microbiota. We showed that exercise within the pool water changed the oral bacteria's relative abundance. To confirm our results and clarify the effect of pool water on oral bacteria relative abundance, more studies on dietary intake should be carried out.